Dosimetric and radiobiologic comparison of 3D conformal, IMRT, VMAT and proton therapy for the treatment of early‐stage glottic cancer. Issue 2 (21st August 2014) - Matthiesen, Chance; Herman, Tania De La Fuente; Singh, Hardev; Mascia, Anthony; Confer, Michael; Simpson, Hilarie; Higby, Christine; Arain, Abeer; Keole, Sameer; Herman, Terence; Bogardus, Carl; Zhao, Yan D.; et al.
Abstract Background This study aims to compare dosimetrically and radiobiologically 3D conformal, intensity modulated radiation therapy (IMRT), RapidArc (RA) volumetric modulated arc therapy and proton therapy techniques for early‐stage glottic cancer. Methods Ten patients were retrospectively selected. Photon treatment planning was performed using Eclipse External Beam Planning, and proton planning was performed using CMS Xio. The minimum, mean and maximum dose values for planning target volume (PTV), mean and maximum dose values for organ at risk, % of volume of PTV receiving at least 95% of the prescription dose, and D20, D50 and D90 of carotid arteries were compared. Biological response models of tumour control probabilities and normal tissue complication probabilities were calculated. Results IMRT, RA and proton plans versus three‐dimensional conformal radiotherapy (3D‐CRT) plans consistently provided superior PTV coverage and decreased mean dose to the thyroid and carotid arteries. Conclusion All these three modalities showed superiority with less variation among themselves compared with 3D‐CRT plans. Clinical investigation is warranted to determine if these treatment approaches will translate into a reduction in radiation therapy‐induced toxicities.